Nutrient subsidy indicators predict the presence of an avian mobile-link species. (June 2018) - Buelow, Christina A.; Baker, Ronald; Reside, April E.; Sheaves, Marcus
Abstract: Island ecosystems can be inordinately dependent on avian nutrient subsidies because of their isolation from external nutrient pools. We investigated relationships between several nutrient subsidy indicators and the presence of Torresian Imperial-Pigeon (TIP, Ducula spilorrhoa ) breeding colonies in island forests of northeast Australia. The following nutrient subsidy indicators were measured in island forest soil and leaf samples: nutrient origin (δN 15 and δC 13 ); total carbon (C), nitrogen (N), and phosphorus (P) levels; and nutrient quality (C:N:P ratios). Random Forest models were used to determine the relative importance of nutrient subsidy indicators for classifying island forests as 'TIP colony present' or 'TIP colony absent'. Total P was the most important soil nutrient subsidy indicator, while δN 15 was the most important leaf nutrient subsidy indicator. Furthermore, in both soil and leaves, δN 15 enrichment and N and P levels increased as the probability of TIP colony presence increased. Measures of nutrient quality also implied plant growth rates were higher in island forests with increased likelihood of TIP colony presence. Torresian Imperial-Pigeons should be classified as an avian mobile-link species with an important role in island ecosystem functioning, encouraging further investigation of the direct and indirect effects associated with TIP nutrient subsidies. This research highlights the importance of understanding the local-scale connectivity processes that underpin the longer distance movements of inter-continental migrants for effective ecosystem management.